The relationship between positive thinking and mental health in cancer patients undergoing therapy - Matthews, Abraham (Jurnal EduHealth, 2024)
The daily life one leads can have adverse effects on the mind that may lead to cancer. Poorly managed cancer can spread and attack other organ tissues aggressively, causing damage to the body's organs. This study aims to analyze the relationship between positive thinking and mental health in cancer patients undergoing therapy. The research involved 100 female participants selected through purposive sampling techniques, conducting an online survey on cancer patients undergoing therapy with an age range of 30 to 50 years. Positive thinking involves positive beliefs about oneself and the future, emphasizing interpreting life in a positive and correct way. Mental health is an individual's mental ability to cope with stress, fostering healthy interpersonal relationships in society and making effective decisions. The results of this study indicate a strong relationship between positive thinking and mental health. This suggests that the higher the level of positive thinking experienced by cancer patients undergoing therapy, the higher their level of mental health. Each cancer patient has a need for a long life, aligned with the quality of their mindset and dietary patterns